Mediastinal Mature Teratoma Revealed by Empyema - Mohammed Raoufi; Laila Herrak; Anas Benali; Leila Achaachi; Mustapha El Ftouh; Salma Bellarbi; Charaf Tilfine; Firdaous Taouarsa (Case Reports in Pulmonology)
Teratomas are germ cell tumors, manifested with a great variety of clinical features; the most common extragonadal site is the anterior mediastinum. In this case, we report the patient with a large mature mediastinal teratoma with several components of ectodermal and endothermal epithelium. A 24-year-old female patient presented with history of persistent chest pain and progressively aggravating dyspnea for the previous 3 months. A chest X-ray showed a large opacity of the entire left hemithorax. Transcutaneous needle aspiration revealed a purulent fluid. The tube thoracostomy was introduced and the effusion was evacuated. Some weeks later, patient was seen in emergency for persistent cough and lateral chest pain. CT scan revealed a mass of the left hemithorax. The mass showed heterogeneous density, without compressing mediastinum great vessels and left hilar structures. Lipase value was elevated in needle aspiration. The patient underwent a total resection of the mediastinum mass via a left posterolateral thoracotomy. Microscopy revealed a mature teratoma with cystic structures. The patient subsequently made a full recovery. This case provide benign mediastinal teratoma with total atelectasis of left lung and elevated lipase value in needle transcutaneous aspiration; this event is explained by pancreatic component in the cystic tumor. Total removal of the tumor is adequate treatment for this type of teratoma and the prognosis is excellent.